The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1177/003335490512000405
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in ADHD and LD in Young School-Age Children: Parental Reports in the National Health Interview Survey

Abstract: Objectives. Racial and ethnic disparities have been documented for many physical health outcomes in children. Less is known, however, about disparities in behavioral and learning disorders in children. This study uses data from a national health survey to examine racial and ethnic differences in identified attention deficit hyperactivity disorder (ADHD) and learning disability (LD). Methods. The 1997–2001 National Health Interview Surveys obtained information from parents about the health and sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 26 publications
(22 reference statements)
6
73
0
1
Order By: Relevance
“…Compared to white parents, AfricanAmericans perceive social stigma with psychopharmacological treatment for ADHD (Davison et al, 2001). Even after controlling for learning disorders, other health conditions, income, and insurance coverage, African-American children had a 40% lower use of medication for ADHD compared to white children (Pastor & Reuben, 2005). Unlike prior research showing African-American parents' lower acceptance and pursuit of medication for their child's ADHD relative to white parents, racial differences were not evident for behavioural therapy (Krain, Kendall, & Power, 2005).…”
Section: Racial Disparities In Views Of Pediatric Psychopharmacologymentioning
confidence: 73%
“…Compared to white parents, AfricanAmericans perceive social stigma with psychopharmacological treatment for ADHD (Davison et al, 2001). Even after controlling for learning disorders, other health conditions, income, and insurance coverage, African-American children had a 40% lower use of medication for ADHD compared to white children (Pastor & Reuben, 2005). Unlike prior research showing African-American parents' lower acceptance and pursuit of medication for their child's ADHD relative to white parents, racial differences were not evident for behavioural therapy (Krain, Kendall, & Power, 2005).…”
Section: Racial Disparities In Views Of Pediatric Psychopharmacologymentioning
confidence: 73%
“…However, lifetime prevalence has been reported to be higher in Latino children outside the United States, ranging from 8% in Puerto Rico (Canino et al 2004) to 17.1% in Colombia (Pineda et al 2001). The National Health Interview Survey reported that the prevalence of ADHD in Latino children living in the United Stated is about half that of Caucasian children (3.3% vs. 6.5%) (Bloom and Tonthat 2002;Pastor and Reuben 2005), but language barriers, physician bias, and different developmental expectations of Latino mothers may account in part for these differences (Stevens et al 2004). One consistent difference between these ethnic groups is the lower rate of access to pharmacological treatments in the Latino population (Jensen et al 1999;Bauermeister et al 2003;Stevens et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…35 Because of small and nonrepresentative samples, previous studies have been limited in their applicability to the gen-eral population. Furthermore, studies [36][37][38] have relied on parent-and teacher-reported cases, which overestimate true prevalence. Accurate estimates of disease burden in a large study population will provide information for determining health care resource allocation for ADHD prevention programs.…”
mentioning
confidence: 99%